Making sense of fatherhood : gender, caring and work - Miller, Tina, 1957- (Cambridge : Cambridge University Press, 2011)
"As family and work demands become more complex, who is left holding the baby? Tina Miller explores men's experiences of fatherhood and provides unique insights into paternal caring, changing masculinities and men's relations to paid work. She focuses on the narratives of a group of men as they first anticipate and then experience fatherhood for the first time. Her original, longitudinal research contributes to contemporary theories of gender against a backdrop of societal and policy change. The men's journeys into fatherhood are both similar and varied, and they illuminate just how deeply gender permeates individual lives, everyday practices and societal assumptions around caring for young children. This book acts as a companion to Making Sense of Motherhood (Cambridge University Press, 2005) and, together, these innovative studies reveal how gendered practices around caring become enacted"--
"This book explores the journeys of a group of men into first-time fatherhood in the UK. It does so at a time when discussions about men and their involvement in family lives -- or lack of involvement -- continue to occupy political debate, newspaper column inches and of course individual and family lives too. Whilst so much around women's lives and motherhood is simplistically assumed, taken for granted and unquestioned, the relationship between men and fatherhood is seen as more problematic: requiring definition, 'claims' and other interventions in order to shape its visibility (or deny it), its dimensions and direction. The parameters of fatherhood are, then, less clearly drawn when set beside those which powerfully and morally encompass motherhood. But both are shaped by the 'choices' and constraints in which gendered lives are lived and which converge on the domains of the home and paid work. These domains provide the settings in which many of the responsibilities associated with motherhood and fatherhood -- caring and providing -- have been understood and practised. Yet these responsibilities and the ways in which they are understood and undertaken are not fixed but rather configured in relation to complex structural, cultural and gendered conditions in an historical moment. In discourses of modern fatherhood in the UK men's involvement in caring for their children has been positioned as (ideally) 'emotionally engaged', 'involved', 'active', 'sensitive' 'intimate' and 'positive' rather than as previously characterised more exclusively in relation to economic provision and the 'breadwinner role' or indeed absence"--
Machine generated contents note: Introduction; 1. Gendered lives and caring responsibilities: an overview; 2. Gendered discourses: men, masculinities and fatherhood; 3. Anticipating fatherhood: 'being there'; 4. Making sense of early fathering experiences; 5. A return to a new normal: juggling fathering and work; 6. Gendering practices: motherhood and fatherhood expectations and experiences; 7. Conclusions and reflections.
Formerly CIP.
Includes bibliographical references (p. 193-203) and index.
Keywords: Fatherhood; Fathers